Improving the transition process to independent living for adolescents with profound intellectual disabilities. Experiences of parents and employees - Eirik Roos; Erik Søndenaa (BMC, 2020)
Abstract Background The transition process from the family home to independent living for young adults with profound intellectual disability (PID) becomes delayed. Those families face challenges that exceed those of typical families such as higher objective and subjective burden, more frequent psychological distress and lower social support. The aim of this study was to explore the collaboration process between parents and employees and identify factors that improve the transition with less burden. Methods A descriptive qualitative study was undertaken with 18 persons (9 parents and 9 employees) interviewed individually and in groups. In accordance with the municipality's guidelines, families with a child with PID should apply for housing, when the child turns 16. The purpose is to ensure interdisciplinary collaboration, information flow and coordinated services according to family's needs. The main question in the interviews was 'What was your experience with cooperation in the transition process, and what would you do to improve this process?' The interviews were analysed with a thematic approach using systematic text condensation. Results The parents experienced a lack of general information about the 'housing waiting list', level of services, and the plan for time of moving from the family home, and how to choose where and whom to live with. Parents described an unsustainable burden of care during the waiting period, and a family crisis caused the allocation of an apartment in a group house. Employees shared challenges to meet families' wishes, as there were too few group homes. They experienced good collaboration with families and said they offered respite care, due to reduce parents' burden of care. Employees experienced that PID adolescents developed skills, mastery and degrees of independence after completing a residency at the Folk High School. Conclusions To improve the transition process from family home to independent living for young adults with PID, the informants highlighted some factors to reduce the burden of care on families: 1) Systematic follow-up program for families to observe their needs at an early stage; 2) More available group houses; 3) Information about the housing priorities of the services and; 4) Educational preparation programs for families.